The grammatical case in Jarir's poetry (Journal of the College of Basic Education, 2022)
In Jarir's poetry, a group of ills were directed at the grammarians from what the Arabs heard from the transmitted with the correct transfer from the definition of the few to the extent of the abundance, and the grammarians resorted to the measuring device in his poetry in Guidance and clarification in referring the branch to the root of the cause, and making the rule of the root to the branch.The immovable is based on the movable if it has its meaning. (1) Our poet excelled in employing analogy in the case of Unable to hear him. He gave the grammarians a range of requirements approved in Jarir's poetry statement, including the agreement of the grammarians' audience.